Perancangan Aplikasi Kamus Air Traffic Control Berbasis Mobile Android - Hondor Saragih; Ajeng Hidayati (CBJIS: Cross-Border Journal of Islamic Studies, 2021)
This study discusses the Air Traffic Controller dictionary where this dictionary will discuss all the initials that have developed in the world of air police, which so far all information about the rules in regulating flights is only in written form (Manual Dictionary). The purpose of this study is to help air transportation speed directors recall some of the existing definitions in the world of aviation, so that it is hoped that there will be no more misunderstandings between pilots and air transportation speed controllers. The method used by the author is the waterfall method, where the flow is Analysis, Design, Implementation and testing. The Unified Modeling Language design will help readers understand this research. The results of this study illustrate that the application can run on an Android mobile device.